An investigation into the effect on cigarette smoking of a new anti-smoking chewing gum - Rosenberg, A (Journal of international medical research, 1977)
A preparation claimed to help patients to break the habit of smoking has recently been introduced. Material released in the mouth from a chewing gum causes an unpleasant taste when tobacco smoke is inhaled. This claim has been investigated in a double-blind trial on sixty subjects, thirty of whom took the active chewing gum and thirty the placebo chewing gum. The subjects each used one piece of chewing gum four times a day over a period of two weeks. This investigation clearly indicates that the active chewing gum is effective as an anti-smoking preparation, when used over a period of two weeks and the effect is still demonstrable one month later, although to a lesser extent.